Vitamin D 20 000 IU per Week for Five Years Does Not Prevent Progression From Prediabetes to Diabetes - Jorde, Rolf; Sollid, Stina T.; Svartberg, Johan; Schirmer, Henrik; Joakimsen, Ragnar M.; Njølstad, Inger; Fuskevåg, Ole M.; Figenschau, Yngve; Hutchinson, Moira Y. S. (The journal of clinical endocrinology and metabolism, 2016)
Context:Vitamin D deficiency is associated with insulin resistance and risk of future diabetes.Objective:The objective of the study was to test whether supplementation with vitamin D to subjects with prediabetes will prevent progression to type 2 diabetes mellitus (T2DM).Design:This was a randomized controlled trial performed in 2008 through 2015.Setting:The study was conducted at the clinical research unit at a teaching hospital.Patients:Five hundred eleven subjects (mean age 62 y, 314 males) with prediabetes diagnosed with an oral glucose tolerance test as part of the Tromsø Study 2007–2008 were included. A total of 256 were randomized to vitamin D and 255 to placebo. Twenty-nine subjects in the vitamin D and 24 in the placebo group withdrew because of adverse events.Interventions:Interventions included vitamin D (cholecalciferol) 20 000 IU/wk vs placebo for 5 years. Annual oral glucose tolerance tests were performed.Main Outcome Measure:Progression to T2DM was the main outcome measure. Secondary outcomes were change in glucose levels, insulin resistance, serum lipids, and blood pressure.Results:The mean baseline serum 25-hydroxyvitamin D level was 60 nmol/L (24 ng/mL). One hundred three in the vitamin D and 112 in the placebo group developed T2DM (hazard risk 0.90; 95% confidence interval 0.69–1.18, Cox regression, P = .45, intention to treat analysis). No consistent significant effects on the other outcomes were seen. Subgroup analyses in subjects with low baseline 25-hydroxyvitamin D yielded similar results. No serious side effects related to the intervention were recorded.Conclusions:In subjects without vitamin D deficiency, vitamin D supplementation is unlikely to prevent progression from prediabetes to diabetes. Very large studies with inclusion of vitamin D-deficient subjects will probably be needed to show such a putative effect.